1991
DOI: 10.1046/j.1468-2982.1991.1101047.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Emotional Precipitation of Migraine and Tension-Type Headache Attacks

Abstract: The frequency of precipitation of headache attacks by individual emotional states as well as the awareness of vulnerability to particular emotional precipitants were investigated in 90 consecutive patients with tension-type headache and 50 consecutive migraine subjects at an Outpatient Headache Clinic. There was differential emotional precipitation in tension-type headache and migraine, with patients with tension-type headache reacting more selectively to negative emotional arousal (anger, anxiety) and reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…An alternative explanation may be co‐occurrence with psychosocial stress, as associations both with chronic headache (Donias et al ., 1991; De Benedittis and Lorenzetti, 1992; Fernandez and Sheffield, 1996; Mitsikostas and Thomas, 1999; Puca et al ., 1999) and musculoskeletal symptoms (Grossi et al ., 1999) have been found. This confounding factor could possibly also explain the strong association between headache and symptoms localized in the abdomen/chest, because more psychiatric disturbance has been found in patients with gastrointestinal pain than amongst patients with back ache (Egan and Betrus, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…An alternative explanation may be co‐occurrence with psychosocial stress, as associations both with chronic headache (Donias et al ., 1991; De Benedittis and Lorenzetti, 1992; Fernandez and Sheffield, 1996; Mitsikostas and Thomas, 1999; Puca et al ., 1999) and musculoskeletal symptoms (Grossi et al ., 1999) have been found. This confounding factor could possibly also explain the strong association between headache and symptoms localized in the abdomen/chest, because more psychiatric disturbance has been found in patients with gastrointestinal pain than amongst patients with back ache (Egan and Betrus, 1987).…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were reported by Donias et al . [20] who found that negative emotions more commonly precipitated TTH than migraine. They suggested that TTH subjects could be having different or defective cognitive schemata that process the given emotional stimuli in their own way to start the pain as compared to migraineurs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with migraine often suffer from a subthreshold but clinically relevant depressive disorder [5, 6]. Other trans-nosographic conditions, described as negative affective states, have been recently investigated in these patients [7], particularly anger expression. It has been suggested that anger may be involved in the etiopathogenesis of migraine [8].…”
Section: Introductionmentioning
confidence: 99%